IMPROVEMENT OF THE ACCOUNTING FOR RECOGNITION OF FINANCIAL INSTRUMENTS - Makhmudov Saidjamol , Kadirjanovich (THE INNOVATION ECONOMY, 2025)
This article discusses the adaptation to international financial reporting standards, the resolution of organizational issues of securities accounting. The digital economy requires the free movement of goods, investments and labor between countries. The development of international relations, the expansion of foreign investment in the economy of the republic, as a result of which the accounting system needs to be improved and adapted to international financial reporting standards. Adaptation to international financial reporting standards, especially the resolution of organizational issues of securities accounting and the organization of audits based on international f inancial reporting standards, is important. Today, improving the legal framework for securities accounting and auditing is becoming an increasingly urgent issue. This is due to the emergence of interaction between companies, enterprises and banks operating in international markets and the further development of the securities market.